1965
DOI: 10.1002/ajpa.1330230215
|View full text |Cite
|
Sign up to set email alerts
|

The microscopic determination of age in human bone

Abstract: The microscopic age changes that occur in human cortical bone were measured by counting the number of osteones, osteon fragments and non‐Haversian canals, and estimating the percentage of lamellar bone in four selected 100 power fields in the outer third of the cortex in ground sections from the mid‐shaft of the femur, tibia and fibula. Age graphs were derived from 126 specimens covering the age range from birth through 95 years. The best correlation with age by regression analysis was found in the osteon frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
324
4
33

Year Published

1973
1973
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 407 publications
(380 citation statements)
references
References 3 publications
14
324
4
33
Order By: Relevance
“…Thus the estimated number of giant canals probably includes some that we would have defined as being too small to be classified as giants. Finally, the relatively few numbers of subjects of each gender within each age group may have resulted in a lack of statistical power for the estimation of parameters such as canal density that in a number of previous studies has been shown to have an age-related pattern (Atkinson, 1965;Currey, 1964;Kerley, 1965Kerley, , 1969). In the current study, this parameter was not influenced significantly by age.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the estimated number of giant canals probably includes some that we would have defined as being too small to be classified as giants. Finally, the relatively few numbers of subjects of each gender within each age group may have resulted in a lack of statistical power for the estimation of parameters such as canal density that in a number of previous studies has been shown to have an age-related pattern (Atkinson, 1965;Currey, 1964;Kerley, 1965Kerley, , 1969). In the current study, this parameter was not influenced significantly by age.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we realized that Kerley's counts of the number of osteons in the outer third of the midshafts of the long bones of 126 normal men as a function of age (25) could be fitted quite accurately by the same single exponential with a A-value of 2-3 %/year. At this point, we decided to set A, the model's rate of compact bone turnover, at 2.5 %/year and to see whether consistent fits could be obtained between all the other parameters and their supporting data.…”
Section: R= E B(t+ E)-b (2)mentioning
confidence: 92%
“…(a) Bone Number of osteons versus age in compact bone (Kerley, 1965). (2s) Tetracycline data for rates of bone formation (Frost, 1969).…”
Section: List Of Datamentioning
confidence: 99%
See 2 more Smart Citations